Conversor SEPIC modificado com acoplamento magnético série e célula multiplicadora de tensão - Kravetz, Fábio Inocêncio (2018)
The renewable energy resources, in special the photovoltaic energy has been achieve more space in last years due to technology advances, cost reduction and decrease of the non-renewable energy sources. The photovoltaic panels in isolation or to small applications generate a low output voltage and to comply with of voltage levels provided in panel’s output to those required by electric power concessionaire is a challenge. In this work is presented a new structure modified of the SEPIC converter topology who uses the coupling magnetic series and voltage multiplier cell techniques together, in order to obtain a high voltage gain aiming at application in renewable energy resources. It was has been choosen non-isolated solution, because this present several advantages in relation to the isolated solution, such as: lower weight, volume, cost and high energy efficiency due to smaller power losses in the coupled inductors. The use leakage inductance, who is an intrinsic parameter of the a magnetic coupling, allows soft-switching operation ZCS in switch, increasing the structure’s efficiency with reduction of switching losses. During the work are perform the analysis of the operation steps of several converters as of the modified SEPIC converter and evolves by addition high voltage techniques until the structure proposed in this work. Finally, is performed the closed loop control using the analog PID controller who provides a fast response and consequent correction to possible changes in the controlled variable. The theoretical and experimental results of the proposed converter are described in this work to validate the developed analysis and demonstrate the structure’s efficiency. The prototype is developed to a application with nominal power of 200 W, nominal output voltage equal 450 V and an input voltage varying between 20 V and 40 V. The efficiency obtained to proposed converter operating in frequency of the 35 kHz in nominal power is 91,28% and efficiency equal 89,04% to nominal power in frequency of the 90 kHz.